Study of the Lightning Overvoltage Protection Effectiveness of High Voltage Mixed Overhead Cable Power Lines - Rafał Tarko; Jakub Gajdzica; Wiesław Nowak; Waldemar Szpyra (Energies, 2021)
In this paper, the effectiveness of lightning overvoltage protection of cables in high voltage overhead cable lines has been analyzed. Because of the high overvoltage level, the cables are protected by surge arresters and by metallic sheath earthing. However, in practice, quite a lot of cases of electricity-evoked damage to the cable outer sheaths are observed, proving that the effectiveness of the protection used is insufficient. As a result, the cables are exposed to environmental factors, especially moisture penetration, which contributes to cable degradation. To explain the causes of this situation, simulation studies were carried out to determine the relevant factors affecting the level of expected overvoltages. The circuit-field model of the overhead cable line in EMTP-ATP, COMSOL and MATLAB software was used for determining overvoltages on the main cable insulation and the outer protective sheath. The studies reveal that the efficiency of the cable insulation overvoltage protection is ensured regardless of the lightning strike location and the crest value of its current. However, the obtained results confirm that no matter the applied protection, the cable outer sheaths may be exposed to overvoltages with higher values than those of the main insulation. Although the analysis was performed for 110 kV lines, the conclusions are general and are also applicable to power lines with higher rated voltages.